Polymeric Nanocomposite Hydrogel Scaffolds in Craniofacial Bone Regeneration: A Comprehensive Review - Maha H. Bashir; Nahed S. Korany; Dina B. E. Farag; Marwa M. S. Abbass; Bassant A. Ezzat; Radwa H. Hegazy; Christof E. Dörfer; Karim M. Fawzy El-Sayed (Biomolecules, 2023)
Nanocomposite biomaterials combine a biopolymeric matrix structure with nanoscale fillers. These bioactive and easily resorbable nanocomposites have been broadly divided into three groups, namely natural, synthetic or composite, based on the polymeric origin. Preparing such nanocomposite structures in the form of hydrogels can create a three-dimensional natural hydrophilic atmosphere pivotal for cell survival and new tissue formation. Thus, hydrogel-based cell distribution and drug administration have evolved as possible options for bone tissue engineering and regeneration. In this context, nanogels or nanohydrogels, created by cross-linking three-dimensional polymer networks, either physically or chemically, with high biocompatibility and mechanical properties were introduced as promising drug delivery systems. The present review highlights the potential of hydrogels and nanopolymers in the field of craniofacial tissue engineering and bone regeneration.